Lycium barbarum and Lactobacillus acidophilus synergistically protect against anti-tuberculosis drug-induced male reproductive injury via gut microbiota-independent pathways in mice - Song, Xiaoyong; Guan, Wei; Du, Zhimin; Gong, Yi; Wang, Dan; Xiong, Yajun; Gao, Yuting; Shi, Xinli (Frontiers in Microbiology, 2025)
BackgroundAs first-line anti-tuberculosis drugs, rifampicin (RIF) and isoniazid (INH) are associated with reproductive impairment during their use, accompanied by sustained dysbiosis of the gut microbiota (GM). Lycium barbarum (Wolfberry), a substance that can be used both as medicine and food, is often used in traditional Chinese medicine to treat male reproductive-related diseases. However, the potential of wolfberry to mitigate reproductive injury induced by anti-tuberculosis (anti-TB) drugs via modulation of the GM has not been reported. This study aimed to explore the protective effect and mechanism of wolfberry on the reproductive injury of male mice induced by anti-TB drugs.MethodsForty male Kunming mice were randomly assigned to normal, model, wolfberry, and levocarnitine groups (n = 10/group). The normal group received a daily gavage of ultrapure water, while the other three groups were administered ultrapure water, wolfberry decoction, and levocarnitine, respectively, via gavage 3 h prior to the daily administration of RIF and INH for 21 days. Another 40 mice were rendered pseudo-germ-free via oral administration of antibiotic (ATB) water for 1 week, then divided into ATB, ATB + Wolfberry, ATB + Lactobacillus acidophilus (L. acidophilus), and ATB + Wolfberry+L. acidophilus groups. Prior to the administration of RIF and INH by gavage, the mice were administered ultrapure water, wolfberry decoction, L. acidophilus, or a combination of wolfberry and L. acidophilus via gavage for 21 consecutive days. Afterwards, sperm motility, count, and serum follicle-stimulating hormone (FSH), luteinizing hormone (LH), and testosterone (T) levels were evaluated. Gut contents were collected for 16S rRNA sequencing and real-time PCR, and testicular tissues were subjected to pathological and transcriptomic analyses.ResultsWolfberry improved sperm quality in mice with reproductive injury induced by anti-TB drugs. Specifically, wolfberry increased sperm count and motility, alleviated testicular pathological damage, and regulated the levels of sex hormones, including FSH, LH, and T. Besides, wolfberry restored intestinal barrier function, enhanced the abundance of L. acidophilus in the gut, and modulated key processes involved in spermatid differentiation, sperm development, and the meiotic cell cycle. Notably, the combination of wolfberry and L. acidophilus yielded the most significant protective effects against reproductive injury induced by anti-TB drugs.ConclusionOur findings suggest that wolfberry protects against reproductive injury induced by anti-TB drugs, partially mediated through modulation of the GM, though this effect is not entirely dependent on the microbiota. Importantly, wolfberry and L. acidophilus play a synergistic role in protecting against the reproductive injury induced by anti-TB drugs.